POLICY IMPLEMENTATION TO ACCELERATE STUNTING REDUCTION: A QUALITATIVE STUDY - Simbolon, Demsa; Maigoda, Tonny Cortis; Meriwati; Efrida, Solha; Yunita; Widiastuti, Heny (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2024)
Background: The prevalence of stunting in Kepahyang Regency in Bengkulu Province is high (24.9%). Despite the policy of Accelerating Stunting Reduction or Percepatan Penurunan Stunting (PPS) outlined in Presidential Decree Number 72 of 2021, results have been suboptimal. Aims: This study aims to analyze and evaluate the implementation of PPS policies and identify supporting and inhibiting factors. Methods: Research using a qualitative approach, focusing on the evaluation of achievements of 11 specific nutrition intervention indicators with policy implementation analysis using the strengthening of Edward III policy analysis. Data collection used in-depth interview guidelines with six stakeholders, focus group discussions (FGD) in two groups, and document observation. Informants are selected by purposive sampling. Data analysis uses content analysis.   Results: The implementation of PPS in Kepahyang Regency faces communication problems, limited resources, complex bureaucratic structures, and inadequate supervision, which shows the need for increased coordination and support. Village government support and good social conditions are supporting factors, while lack of communication between the village government and the community and minimal budget support are the main obstacles.   Conclusion: Communication issues, resource limitations, bureaucratic complexity, and inadequate supervision are the inhibiting factors. Strong support from local government and health workers is the supporting factor. Keywords: implementation, policy, specific nutrition interventions, stunting